Altered cellular metabolism following traumatic brain injury: a magnetic resonance spectroscopy study. - Garnett, MR; Corkill, R; Blamire, A; Rajagopalan, B; Manners, D; Young, J; Styles, P; Cadoux-Hudson, T (2001)
Experimental studies have reported early reductions in pH, phosphocreatine, and free intracellular magnesium following traumatic brain injury using phosphorus magnetic resonance spectroscopy. Paradoxically, in clinical studies there is some evidence for an increase in the pH in the subacute stage following traumatic brain injury. We therefore performed phosphorus magnetic resonance spectroscopy on seven patients in the subacute stage (mean 9 days postinjury) following traumatic brain injury to assess cellular metabolism. In areas of normal-appearing white matter, the pH was significantly alkaline (patients 7.09 +/- 0.04 [mean +/- SD], controls 7.01 +/- 0.04, p = 0.008), the phosphocreatine to inorganic phosphate ratio (PCr/Pi) was significantly increased (patients 4.03 +/- 1.18, controls 2.64 +/- 0.71, p = 0.03), the inorganic phosphate to adenosine triphosphate ratio (Pi/ATP) was significantly reduced (patients 0.37 +/- 0.10, controls 0.56 +/- 0.19, p = 0.04), and the PCr/ATP ratio was nonsignificantly increased (patients 1.53 +/- 0.29, controls 1.34 +/- 0.19, p = 0.14) in patients compared to controls. Furthermore, the calculated free intracellular magnesium was significantly increased in the patients compared to the controls (patients 0.33 +/- 0.09 mM, controls 0.22 +/- 0.09 mM, p = 0.03)). Proton spectra, acquired from similar regions showed a significant reduction in N-acetylaspartate (patients 9.64 +/- 2.49 units, controls 12.84 +/- 2.35 units, p = 0.03) and a significant increase in choline compounds (patients 7.96 +/- 1.02, controls 6.67 +/- 1.01 units, p = 0.03). No lactate was visible in any patient or control spectrum. The alterations in metabolism observed in these patients could not be explained by ongoing ischemia but might be secondary to a loss of normal cellular homeostasis or a relative alteration in the cellular population, in particular an increase in the glial cell density, in these regions.